Bananas, the GATT, the WTO and US and EU domestic Politics - Jaime de Melo (Fondation pour les études et recherches sur le développement international (FERDI), 2012)
This paper revisits the celebrated conflict that lasted close to two decades and pitted the EU against the US and against MFN suppliers of bananas. It starts by recalling the major turning points in the dispute and argues that the EU-US conflict could largely be explained by the changing landscape on trade-policy making on both sides of the Atlantic. As to the EU-MFN grower dispute, it can be largely explained by uncertainty on the distribution of quota rents and on the reluctance to use economic analysis in the panel decisions. Econometric and simulation estimates are given in support of this argument.
Keywords: F11; F15; 330; preferences; Tariff-rate quotas; bananas; political economy